Irrational use of Eucalyptus oil in dentistry: a case report - Shishir, RS; Renita, C; Kumuda, AR; Subhas, BG (Bangladesh Journal of Medical Science, 2011)
Use of herbal medicaments for dental pain is a practice still followed in some parts of rural India. Most often these herbal medicines are readily available to the rural without the prescription from an authorized practitioner. Eucalyptus oil is one such herbal drug which is widely used for a number of ailments. An unusual and a rare case of chemical injury secondary to the use of eucalyptus oil has been presented here. We have also described the management of the injury with herbal medication. This case report tends to highlights the dangers of self medication and also stresses on the role of herbal medications in dentistry. Keywords: Eucalyptus oil; chemical ulcers; acacia catechu; dentistry. DOI: http://dx.doi.org/10.3329/bjms.v10i2.7807 Bangladesh Journal of Medical Science Vol.10 No.2 Apr’11 pp.121-124